Pulmonary hemorrhage and associated risk factors among newborns admitted to a tertiary level neonatal unit in Botswana - Gezmu, Alemayehu Mekonnen; Tefera, Endale; Mochankana, Kagiso; Imran, Fizzah; Joel, Dipesalema; Pelaelo, Irene; Nakstad, Britt (Frontiers in Pediatrics, 2023)
Introduction Pulmonary hemorrhage is a life-threatening complication seen in very sick newborns with high morbidity and mortality. There is little data on the incidence, risk factors and ultimate survival of newborns with pulmonary hemorrhage in sub-Saharan countries, where the healthcare provision and facility differ in many ways compared to high-income countries. Hence, this study aimed to determine the incidence, identify risk factors, and describe outcome of pulmonary hemorrhage in newborns in a low-middle income country setting. Methods and materials A cohort study with prospective data collection was conducted in a public, tertiary level hospital in Botswana, the Princess Marina Hospital (PMH). All newborns admitted in the neonatal unit from 1st January 2020 to 31st December 2021 were included in the study. Data were collected using check list developed on RedCap database (https//: ehealth.ub.ac.bw/redcap). Incidence rate of pulmonary hemorrhage was calculated as the number of newborns who had pulmonary hemorrhage per 1,000 newborns in the two-year period. Group comparisons were made using X2 and student t-test. Multivariate logistic regression was used to identify risk factors independently associated with pulmonary hemorrhage. Result There were 1350 newborns enrolled during the study period. Male newborns were 729(54%). The mean (SD) birthweight was 2154(+997.5) gram, and gestational age 34.3(+4.7) weeks. Eighty percent of the newborns were delivered in the same facility. The incidence of pulmonary hemorrhage was 54/1350 (4% [95% CI (3-5.2%)] among the newborns admitted in the unit. Mortality rate in those diagnosed with pulmonary hemorrhage was 29/54 (53.7%). Multivariate logistic regression identified birthweight, anemia, sepsis, shock, disseminated intravascular coagulopathy (DIC), apnea of prematurity, neonatal encephalopathy, intraventricular hemorrhage, mechanical ventilation, and blood transfusion as risk factors independently associated with pulmonary hemorrhage. Conclusion This cohort study identified high incidence and mortality rate of pulmonary hemorrhage in newborns in PMH. Multiple risk factors such as low birthweight, anemia, blood transfusion, apnea of prematurity, neonatal encephalopathy, intraventricular hemorrhage, sepsis, shock, DIC and mechanical ventilation were identified as independently associated risk factors for PH.